Marketing strategy for promoting the Erasmus+ programme - Nagy, Szabolcs; Pererva, P. G. (WSEH, 2025)
The Erasmus+ programme, as a flagship initiative of the European Union, requires a comprehensive marketing strategy to enhance its visibility and accessibility among target audiences. Effective promotion involves the integration of digital communication tools, social media campaigns, and institutional partnerships to highlight opportunities for mobility, cooperation, and skills development. By applying market segmentation, branding techniques, and stakeholder engagement, the strategy ensures that the programme reaches diverse groups of students, educators, and organizations. Continuous monitoring of outreach effectiveness and adaptation to evolving educational trends further strengthens the impact of Erasmus+, fostering international collaboration and reinforcing its role in shaping a competitive knowledge-based society.
Keywords: marketing; marketing strategy; Erasmus+ programme; educational environment; competition; globalization; international mobility; educational cooperation; branding; stakeholder engagement; digital communication; knowledge society